EVALUASI PENGGUNAAN SISTEM INFORMASI “TEAMMATE” DALAM PELAKSANAAN TUGAS AUDIT PADA INSPEKTORAT JENDERAL KEMENTERIAN KEUANGAN - Aditya Yuda Krisnanto Putra (Jurnal Akuntansi Universitas Jember, 2016)
This research is motivated by the use of technology is considered important because it can help the activity or activities of the o.rganization, including the audit field through the use of the Audit Management System (AMS) where the organization is required to prepare a mechanism/infrastructure of modern information technology-based.